2013
DOI: 10.4103/0970-9371.126640
|View full text |Cite
|
Sign up to set email alerts
|

Subclassification of pulmonary non-small cell lung carcinoma in fine needle aspirates using a limited immunohistochemistry panel

Abstract: Background:Newer treatment modalities require subtyping of non-small cell lung carcinomas (NSCLC). Morphological differentiation is often difficult and various immunohistochemical (IHC) panels have been used to maximize the proportion of accurately subtyped NSCLC.Aim:The aim of this study was to subtype NSCLC on fine needle aspirates (FNA) using a minimal antibody panel.Materials and Methods:Cell blocks from 23 FNA samples with a morphological diagnosis of NSCLC were taken. IHC was evaluated (blinded to clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…The expression patterns of TTF-1 protein and mRNA in the present study are consistent with those of our previous studies (10,11). TTF-1 and p63 immunostaining has been utilized successfully in previous studies (20,21) to facilitate pathological differentation between small cell carcinoma and poorly differentiated pulmonary SCC using cytological samples. Kapila et al (20) were able to catergorize NSCLC samples using a restricted panel of antibodies.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The expression patterns of TTF-1 protein and mRNA in the present study are consistent with those of our previous studies (10,11). TTF-1 and p63 immunostaining has been utilized successfully in previous studies (20,21) to facilitate pathological differentation between small cell carcinoma and poorly differentiated pulmonary SCC using cytological samples. Kapila et al (20) were able to catergorize NSCLC samples using a restricted panel of antibodies.…”
Section: Discussionsupporting
confidence: 80%
“…TTF-1 and p63 immunostaining has been utilized successfully in previous studies (20,21) to facilitate pathological differentation between small cell carcinoma and poorly differentiated pulmonary SCC using cytological samples. Kapila et al (20) were able to catergorize NSCLC samples using a restricted panel of antibodies. The authors were also able to differentiate between adenocarcinoma and SCC samples.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kusum Kapila et al CK5/6 showed a sensitivity and specificity of 53% and 96% respectively and TTF-1 was found to be most specific marker for adenocarcinoma with 60% sensitivity and 98% specificity. [25] Another study by Gregorz T Gurda et al in 72 cases of primary adencarcinoma TTF-1 showed a sensitivity and specificity of 84.5% and 96.4% respectively. In 30 cases of squamous cell carcinomaCK5/6 showed a sensitivity and specificity of 100% and 77.8% respectively [26].…”
Section: Discussionmentioning
confidence: 94%
“…With the advent of targeted therapy for advanced lung carcinomas and significant differential response to them, it is recommended to further classify NSCLC into Adenocarcinoma and Squamous cell carcinoma based on morphology and ancillary techniques like IHC [immunohistochemistry] for the eligibility to Targeted therapy. [19,20] When the morphological criteria of Squamous cell carcinoma and Adenocarcinoma were present, diagnosis can be easily established. When the tumour does not show the classical morphological criteria, immunohistochemical work up is necessary for further typing.…”
Section: Thoracocentesismentioning
confidence: 99%